The Impact of Motivation, Perception and Attitude toward Consumer Purchasing Decision: A Study Case of Surabaya and Jakarta Society on Carl’s Junior - Steffi Gunawan (iBuss Management, 2015)
Psychological factors such as consumer motivation, perception and attitude are believed to be the main decider of consumer purchasing decision. Those psychological factors will process all the stimulators from the marketers then affect the entire consumer decision-making process. Carl’s Junior is one of the most happening restaurants that able to attract many Surabaya and Jakarta citizen dare to queue just to enjoy a burger. This research wants to  find out the impact of consumer motivation, perception an attitude toward consumer purchasing decision as well as to compare Surabaya and Jakarta consumer behavior on purchasing Carl’s Junior. Consumer motivation is here divided into hierarchy of needs, rational motivation and emotional motivation. Consumer perception is here divided into perceived image, perceived quality and perceived risk. Multiple regression test is used to process the result and the researcher use simple random sampling by spreading 100 questionnaires to each Jakarta and Surabaya Carl’s Junior consumers. The result of the research shows that there is significant impact of consumer motivation, perception and attitude toward consumer purchasing decision and there are similarity and differences consumer behavior between Surabaya and Jakarta consumer.   Keywords: Consumer behavior, motivation, perception, attitude, consumer purchasing decision.